An insect-scale robot reveals the effects of different body dynamics regimes during open-loop running in feature-laden terrain. (3rd February 2022) - Schiebel, Perrin E; Shum, Jennifer; Cerbone, Henry; Wood, Robert J
Abstract: The transition from the lab to natural environments is an archetypal challenge in robotics. While larger robots can manage complex limb–ground interactions using sensing and control, such strategies are difficult to implement on small platforms where space and power are limited. The Harvard Ambulatory Microrobot (HAMR) is an insect-scale quadruped capable of effective open-loop running on featureless, hard substrates. Inspired by the predominantly feedforward strategy of rapidly-running cockroaches on uneven terrain (Sponberg, 2007), we used HAMR to explore open-loop running on two 3D printed heterogeneous terrains generated using fractional Brownian motion. The 'pocked' terrain had foot-scale features throughout while the 'jagged' terrain features increased in height in the direction of travel. We measured the performance of trot and pronk gaits while varying limb amplitude and stride frequency. The frequencies tested encompassed different dynamics regimes: body resonance (10–25 Hz) and kinematic running (30–40 Hz), with dynamics typical of biological running and walking, respectively, and limb-transmission resonance (45–60 Hz). On the featureless and pocked terrains, low mechanical cost-of-transport (mCoT) kinematic running combinations performed best without systematic differences between trot and pronk; indicating that if terrain features are not too tall, a robot can transition from homo-to heterogeneous environments in open-loop. Pronk bypassed taller features than trot on the jagged terrain, and higher mCoT, lower frequency running was more often effective. While increasing input power to the robot improved performance in general, lower frequency pronking on jagged terrain allowed the robot to bypass taller features compared with the same input power at higher frequencies. This was correlated with the increased variation in center-of-mass orientation occurring at frequencies near body resonance. This study established that appropriate choice of robot dynamics, as mediated by gait, frequency, and limb amplitude, can expand the terrains accessible to microrobots without the addition of sensing or closed-loop control.